Residual transmission of HIV infection from mother to child in the Atlantic and littoral departments in Benin - Edwige Hermione Dagba Gbessin; Haziz Sina; René Kpemahouton Keke; Michel Kiréopori Gomgnimbou; Aldric Afangnihoun; Moussa Bachabi; Abdoul-Salam Ouedraogo; Lamine Baba-Moussa (BMC Pediatrics)
Abstract Background The implementation of the WHO’s 2015 recommendations in Benin, requires an assessment of the progress made over time in preventing the transmission of the infection to exposed-infants, and the identification of its determinants. Methods This was a retrospective study of HIV-1 exposed-infants who underwent PCR between the 6th and 8th weeks of life. Early diagnostic tests were performed using the Abbott m2000 RealTime platform. Comparison of proportions tests (analysis of the significance of the difference in prevalence) with an error threshold of 5% were used to assess the determinants of the transmission. Statistical analysis was performed using R statistical software, version 4.1.3.0. Results A total of 5,312 infants benefited from early diagnosis by PCR between 2016 and 2021. Among them, 52% are males, tritherapy before pregnancy was the majority treatment used by mothers (30.6%) and monotherapy that of newborns (70%). Mixed breastfeeding is the feeding method with the highest prevalence. The overall transmission rate was 3.4% over the six years. The highest prevalence was achieved in 2018 (4.2%) and the lowest in 2021 (2.7%). The prevalence was lower when mothers were on tritherapy before pregnancy. The determinants of transmission were: mixed breastfeeding, lack of treatment in mothers (22.4%), lack of treatment in infants (19.7%), undefined treatments or absence of treatment in the mother-child pair. Conclusion This study shows the contribution over time of the PMTCT program to reducing HIV transmission among exposed-infants and also underlines the need for proper conduct of treatment in any women of childbearing age.